(untitled) (Analysis in Theory and Applications, 2023)
Let P be the classical Hardy operator on (0, ∞) and Q be the adjoint operator. In this paper, we get the boundedness for P, Q and the commutators of P and Q with CMO functions on the weighted Herz spaces.